Design and Build Virtual Tour Exhibition Application at INKINDO East Java - Jalu Sakti, Arjun Adi Luhung; Firdaus, Muhammad (Raudhah Publisher, 2024)
This study aims to design and develop a web-based Virtual Tour Exhibition application to support the promotion and introduction of the Indonesian Consultants Association (INKINDO) East Java. The application leverages 3D Vista Virtual Tour technology to create an interactive exploration experience for users. The development process follows the Waterfall methodology, encompassing requirements analysis, design, implementation, and testing stages. Testing was conducted using the Blackbox method to evaluate system functionality and the System Usability Scale (SUS) to assess user satisfaction. The results indicate that the application effectively meets user needs with optimal functionality and achieves a high SUS score, reflecting significant user satisfaction.